High-temperature exposure alters the community structure and functional features of the intestinal microbiota in Shaoxing ducks (Anas platyrhynchos) - Tian, Yong (Poult Sci, 2020)
The gut microbiome is a complex ecosystem that contributes to host nutrition and health. However, our current knowledge of the relationship between ambient temperature and gut microbiota of poultry is still limited. The objective of the present study was to characterize the intestinal microbiota of ducks exposed to high ambient temperature. Sixty 60-day-old Shaoxing ducks were allocated to control and heat-treated groups. The ducks in the control group were kept at 25°C, and the ducks in the heat treatment group were raised at 30–40°C, which simulated the temperature change of day and night in summer. After 15 D, the intestinal contents of the duodenum, jejunum, and ileum were obtained from 6 ducks of each group. Genomic DNA was extracted and amplified based on the V4–V5 hypervariable region of 16S rRNA. The results showed that Firmicutes was the dominant bacterial phylum with the highest abundance in the contents of the small intestine of ducks, and the relative abundance of the phylum Firmicutes in all 3 intestinal segments was increased by high temperature. At the genus level, Lactobacillus was found to be the most dominant bacterial genus across 3 gut segments, and its abundance was increased in ducks under heat treatment. Compared with the corresponding intestine segment of control ducks, a total of 36 genera in the duodenum, 19 genera in the jejunum, and 6 genera in the ileum of heat-treated ducks were found to be significantly different in the abundance (linear discriminant analysis score >3.0, P < 0.05). Functional prediction of gut microbiota revealed that high temperature caused changes in the abundance of metabolism and transcription-related pathways. It is noteworthy that most of the altered pathways are related to metabolism. In conclusion, high temperature induced remarkable taxonomic changes in the gut microbiome of ducks, which might be related to the negative effects of high temperature in ducks. Our present study provided an important theoretical ground for high-temperature intervention.